STUDI KOMPARASI PEMANFAATAN LAHAN PEKARANGAN MASYARAKAT NAGARI AMPING PARAK DENGAN NAGARI SURANTIH DI KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Putri, Septi Guzali (Pendidikan Geografi, 2014)
This study is motivated by two Nagari Amping Parak and Nagari Surantih. Where Nagari Amping Parak have started utilizing such yards, Apotik life, and ornamental plants. While in Nagari Surantih less well in land use her yard as much visible vacant land around the yard, but if used in the best possible people can grow a variety of plants such as herb, herbs, and ornamental plants. The research is a comparative descriptive. The population in this study were all families (KK) contained in Nagari Surantih and Nagari Amping Parak totaling 4872 families (KK). Samples were taken in two ways, the sample region taken by purposive sampling technique that is an area that has quite extensive yard area and that most households Nagari Surantih and Nagari Amping Parak. The sample of respondents was taken with rondom purposive sampling technique with 5% Proportion that survey respondents totaled 110 households. Analysis using percentages and the t test. Results of the study found that: 1) there is no difference between the level of public education Nagari Surantih and Nagari Amping Parak because the t value is smaller than t table (0.200 <1.662), means that the hypothesis is rejected, 2) there is no difference between public land ownership Nagari Amping Parak and Nagari Surantih because the t value is smaller than t table (-0.03 <1.662), means that the hypothesis is rejected, and 3) there is a difference between free time Nagari Surantih and Nagari Amping Parak because as the value of t is greater than t table (2.206> 1.662), time to spare villagers Amping Parak greater than Surantih Nagari community. Means the hypothesis is accepted. In conclusion, from the results of the study found that there were no differences in levels of public education, and public land ownership differences Nagari Amping Parak and Nagari Surantih, there is a difference leisure time community and Nagari Surantih and Nagari Amping Parak.